Social constructivism as an inquiry paradigm: understanding performance measurement practice in central government - Abdullah, Nur Anisah (2011)
The purpose of this paper is to discuss the subscription to social constructivism as an inquiry paradigm to explore performance measurement issues faced by government agencies and public bodies with a view towards improvement. The paper presents the use of phenomenology to understand performance measurement practice in central government using in-depth interviews with twenty-two individuals. The participants were asked two broad questions: What worked well in terms of performance measurement with this organisation? What did not work very well? Their answers led to more specific questions providing rich data on their experiences generating an understanding of the common practice of performance measurement. The phenomenology was a useful approach in teasing out the ‘common sense of performance measurement’ from respondents of which otherwise taken for granted. The success of phenomenology and in-depth interviews rests heavily on researcher’s interviewing skills in drawing the details from interviewees, when and how to probe into certain aspects; and their data analysis ability in identifying, interpreting, clustering and exploring the links and relationship between emerging themes. The test would be: Have we enough data to explain the phenomenon? Can we explain the relationships between emerging themes? Have we enough evidence in constructing a convincing argument? The paper summarises the step-by-step approach to data analysis procedure in guiding phenomenology research and ends with lessons learned.